“ALLE DE SOM SITTER HER, HAR EN NY MULIGHET” PERSPEKTIVER PÅ PÅVIRKNING OG UTVIKLING AV FENGSLEDE I NORSKE HØYSIKKERHETSAVDELINGER - redwall, Terje Emil (Psyke & Logos, 2015)
Perspectives on impacts on and the development of prisoners in Norwegian high-security wings. Rehabilitation and improvement of a prisoner are at the center of the discourse of correctional services in Norway. It is investigated in this article how the task of rehabilitation and improvement during imprisonment is understood and interpreted by prison officers who are responsible for guarding, handling and interacting with the prisoners in Norwegian high-security wings. Firstly, I will describe how punishment is justified in the criminal justice literature and in policy documents in the perspective of the so-called improving effects of punishment. After the presentation of data materials and method, I present two different approaches in the prison officers’ affecting and organizing work with prisoners. One approach emphasizes that the work of prison officers contains a correctional element; the officers should practice their role with a conscious intention of transmitting a set of values, attitudes and skills to the inmates. The other focuses on the officers’ role as an organizer of opportunities and ways to create better living conditions for the prisoners. Here the attention is primarily on the inmate’s future, on how things will be for them when they are released from prison: if, for example, they have jobs to go to and/or have a permanent place to live. The article ends with some value-oriented reflections on these two approaches.